Staggering and Synchronization in Price-Setting: Evidence from Multiproduct Firms - Lach, Saul; Tsiddon, Daniel (American Economic Review, 1996)
Theoretical work on price-setting behavior focuses on the single-product case while, in reality, a single price-setter sells many products. We use retail store-level multiproduct pricing data to learn about price dynamics. We find that, while the timing of a product's price changes is staggered across stores selling the same product, the timing of the price changes of different products sold within the same store is highly synchronized. This finding validates the usual assumption that decisions are staggered across price-setters and suggests that price rigidity is due mostly to "mechanical" reasons and not to informational asymmetries.